HISTORICAL BACKGROUND AND DEVELOPMENT OF ENGLISH AND UZBEK LEXICOGRAPHY - Jurayeva , Sarvinoz Xayrulla qizi (Educational Research in Universal Sciences, 2023)
In this article, it will be presented the common linguistic terms as a lexicographic way. It is widely acknowledged that compilation of any kind of dictionaries can be more helpful and easiest way in language teaching, learning or using it another reasons in linguistics and each of them has its own historical development. As lexicography deals with all dictionary compiling processes, it will be investigated enrichment period of linguistic terms with the implementation of lexicography in both English and Uzbek languages.